Parental Efficacy as a Predictor of Mothers’ Intentions to Educate Intellectually Disabled Children on Sexual Abuse Prevention - Nisaul Maghfiroh (Al Huwiyah: Journal of Woman and Children Studies, 2025)
Children with intellectual disabilities are three times more likely to experience sexual violence than typically developing children. Given the serious negative consequences, early prevention efforts are essential, particularly by empowering parents as primary agents in educating self-protection. This study aims to examine the role of parenting efficacy and reproductive health knowledge in predicting mothers’ intention to teach self-protection against sexual violence to their children with intellectual disabilities. The sample consisted of 121 mothers of children with intellectual disabilities attending special education schools (SLB) in Yogyakarta. A quantitative survey method was employed, using a parenting efficacy scale, a reproductive health knowledge test, and a scale measuring the intention to teach self-protection. Regression analysis revealed that parenting efficacy and reproductive health knowledge jointly predicted mothers’ intention significantly (p < 0.05). However, only parenting efficacy emerged as a significant individual predictor. These findings highlight the critical role of mothers’ confidence in their parenting ability as a key factor in preventing sexual violence among children with special needs. Keywords: parenting efficacy, knowledge of reproductive health, intention to teach self protection from sexual violence, mental retardation